PS-078 Impact of the certification process on the assessment of the medication system at a University Hospital. (24th February 2014) - Promis, A; Bigot, A; Cool, C; Lebaudy, C; Irazusta, O; Le Floch Meunier, B; Massip, P; Cestac, P
Abstract : Background: In September 2012 Toulouse Hospital was inspected to evaluate its quality according to the French Health Authority standards. This process covers all aspects of the hospital including the medication system (MS) which is responsible for the prescription, distribution, pharmaceutical analysis and administration. Purpose: To verify that the actions put in place before the audit were still in effect. Materials and methods: From February to August 2012, risk mapping was conducted in 32 randomly selected units using a tool created by the National Agency for Quality and Performance. The tool, called "InterDiag Medicaments", includes 160 questions that cover all steps of the MS. Corrective actions were put in place following the risk mapping analysis. From January to September 2013, the process was repeated, this time in 25 randomly selected wards. Results: The analysis of the two sets of results (2012 and 2013) showed that there was no difference between the mean structural risk: 63% (50 to 92%) in 2012 and 63% (43 to 86%) in 2013. For the "Prevention" step, the mean risk rose from 51% in 2012 to 64% in 2013 (p = 0.068). This improvement is attributed to an increase in "Experience feedback" and an improvement in the knowledge of protocols between 2012 and 2013. Concerning the "Management of the medicines storage cabinets", the risk control percentage increased from 58% in 2012 to 64% in 2013. Improvements were also seen in "Prescription and dispensing", and "Preparation and administration", from 51% to 56% and 68% to 73% respectively. Conclusions: These results help to confirm the positive effects of certification. The self-assessment tool helps professionals to take a proactive and system-based approach to the MS. Risk mapping is currently being performed in other units. No conflict of interest.